Maqasid Al-Qur’an in the Face of Contemporary Legal Challenges: An Epistemological Study on the Implementation of the Aceh Qanun Jinayat in Indonesia's Public Sphere - Siti Aisyah (Jurnal Indonesia Sosial Sains, 2026)
This study aims to explain how maqāṣid al-Qur’ān can be used as an epistemological framework to assess the implementation of the Aceh Criminal Code in the context of the Indonesian public sphere. This issue is important because the qanun is often debated between the legitimacy of local autonomy, the moral demands of the Acehnese people, and modern human rights criticism. This study uses a qualitative-epistemological approach by combining content analysis of Qanun No. 6 of 2014, a literature review of research conducted over the past five years, thematic analysis, and a socio-legal approach to map the relationship between Sharia norms, legal practices, and social dynamics. The results show that qanun has strong historical and political legitimacy and is viewed by the community as an instrument for maintaining moral order and social cohesion after the conflict. From the maqāṣid perspective, qanun can be categorized as an effort to protect religion, life, and public honor, especially when implemented through educational and preventive mechanisms. However, the study also found that alignment with maqāṣid is highly dependent on procedural quality, operational standards, victim protection, and moderation of implementation. This study concludes that reforming implementation is the most maqāṣidi step to ensure substantive justice and protection of human dignity in Aceh.